2023
DOI: 10.3390/ma16124334
|View full text |Cite
|
Sign up to set email alerts
|

Improving of 100Cr6 Steel Corrosion and Wear Properties in Simulated Sea Water Environment by Tungsten-Doped DLC Coating

Abstract: A progressive type of tungsten-doped DLC coating was applied to a quenched and tempered 100Cr6 steel with the aim to improve the wear and corrosion properties in simulated seawater conditions and to compare the performance to conventional DLC coating. Tungsten doping caused a shift of the corrosion potential (Ecorr) to a lower negative value of −172 mV, while the conventional DLC exhibited an Ecorr of −477 mV. In dry conditions, the W-DLC coefficient of friction is slightly higher than that of the conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Among various coatings, diamond-like carbon (DLC) coatings are extensively used as scratch-resistant and anti-corrosion coatings for metal materials due to their high hardness and excellent chemical stability [10][11][12][13][14]. Recent efforts have seen a surge in the exploration of various DLC coatings for application in marine environments, showcasing enhanced performance over short durations [15,16]. For example, Totolin et al found that the W-doped DLC coatings could effectively improve the tribocorrosion performance of the substrates in artificial seawater within 4.5 h [17].…”
Section: Introductionmentioning
confidence: 99%
“…Among various coatings, diamond-like carbon (DLC) coatings are extensively used as scratch-resistant and anti-corrosion coatings for metal materials due to their high hardness and excellent chemical stability [10][11][12][13][14]. Recent efforts have seen a surge in the exploration of various DLC coatings for application in marine environments, showcasing enhanced performance over short durations [15,16]. For example, Totolin et al found that the W-doped DLC coatings could effectively improve the tribocorrosion performance of the substrates in artificial seawater within 4.5 h [17].…”
Section: Introductionmentioning
confidence: 99%
“…The extended life of the components is a constantly evolving topic [6]. Improvements in functional properties are achieved through the use of conventional and unconventional technologies, which include laser and electrical discharge machining, electrochemical and chemical deposition, additive technologies (3D printing) [7], and modern methods of coating deposition by vacuum techniques [8][9][10], such as CVD and PVD gas-phase deposition [11], often further assisted by plasma [11][12][13], or ALD atomic layer deposition [14]. The main advantage of these methods is the improvement obtained in the material properties without changing its dimensions.…”
Section: Introductionmentioning
confidence: 99%